Belief systems in administration and training - Sykes, Wilbert R. (Journal of religion and health, 1989)
Belief systems are instruments for observing events, classifying information, communicating with others, and doing therapy. A belief system is a combination of feelings, thoughts, actions, and expectations. Belief systems operating in the training environment affect how therapists are able to deal with transference and countertransference. Belief systems must be evaluated in terms of whether they are comprehensive, delusional, absent, sinelusional, and the extent to which they are structuring us. The use of belief systems provides us with an appreciation of our own activities, an instrument for conveying our feelings, and, most importantly, a means for understanding the views of others.